Symptomatic Tachydysrhythmias after Esophagectomy: Incidence and Outcome Measures - Amar, D. (Institutional Knowledge at Singapore Management University, 1996)
Supraventricular tachydysrhythmias (SVT) after esophageal operations for carcinoma occur frequently and may be associated with increased morbidity. Prospective data on the etiology, incidence, and importance of these dysrhythmias are sparse. Methods. In 100 consecutive patients undergoing esophagectomy without prior history of atrial dysrhythmias or receiving antiarrhythmics, we prospectively examined the effects of predefined risk factors by history and pulmonary function on the 30-day incidence of symptomatic postoperative SVT, need for intensive care unit admission, and mortality rate. Results. Symptomatic postoperative SVT occurred in 13 (13%) of the 100 patients studied at a median of 3 days after operation and was accompanied by hypotension in 9/13 (69%). Univariate correlates of SVT were older age (p = 0.03), perioperative use of theophylline (p = 0.044), and a low carbon monoxide diffusion capacity (measured in 56% of patients) on preoperative pulmonary function. Patients in whom SVT developed had a higher rate of intensive care unit admission (p = 0.0001) and a longer hospital stay (p = 0.036). Although patients in whom SVT developed had a higher (p = 0.013) 30-day mortality rate, SVT was not the direct cause of death. Conclusions. These prospective data show that the true incidence of symptomatic SVT within 30 days of esophagectomy is lower than previously reported. Occurrence of SVT was associated with significant morbidity. Older age was the strongest predictor of SVT after esophagectomy. In high-risk patients, continued monitoring (48 to 72 hours) and early interventions to decrease the incidence of postoperative SVT may improve overall surgical outcomes.